Reinforcement of the Cadres’ Role of Toddler Integrated Healthcare Center to Prevent Stunting During the Covid-19 Pandemic - Nita Arisanti Yulanda; Titan Ligita; Cindiarty Kurnia Saputri; Sukmawati Sukmawati; Kharisma Aji Martadi (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Integrated Healthcare Center, commonly known as Posyandu, is a form of a community resource health service system that is managed and organized from, by, for, and with the community. The idea is to develop and grow Posyandu as one of the indicators of community health empowerment. Through the attempt of human resource quality development, in this context was Posyandu cadres, Posyandu activities during the COVID-19 Pandemic had become a challenge for the cadres in carrying out their role. Therefore, health protocol was prioritized to upkeep Health and safety in general. Community service activities carried out by organizing group socialization for Toddler Posyandu cadres had become a strategy to improve cadres’ knowledge and skills in managing Posyandu activities. Test results of pretest and post-test analysis (?= 0,017) show a difference between before and after the mentoring. The Posyandu cadres are expected to be able to implement the knowledge they get during socialization.